Method of manufacturing and reinforcing a plurality of asphalt and concrete structures - Muniandy, Ratnasamy; Ahmad, Nadzrol Fadzilah; Hassim, Salihudin (2012)
A method of manufacturing and reinforcing multiple concrete structures for roadways, driveways, walkways and like surfaces, includes the steps of determining multiple voids in mineral aggregates in at least one of multiple concrete structures, selecting multiple beads based on size of multiple voids in mineral aggregates, mixing multiple linking material to multiple beads and a first mixture for filling up multiple voids in mineral aggregates, applying heat to form a mineral aggregated reinforcing mixture between the first mixture, multiple beads and multiple linking material and applying the mineral aggregated reinforcing mixture to a surface to be paved.